Examining the gender of sources in media releases: does the CEO matter? - Fussell Sisco, Hilary and Zoch, Lynn M. and Collins, Erik (2010)
"The impetus for the Sisco, Zoch and Collins article study came from research indicating that reporters seem more likely to quote male sources than female sources. The question for the researchers then became whether we, as public relations practitioners, are causing some of this imbalance by providing reporters with a disproportionate number of male sources. The primary purpose of the research presented in this article was to turn the tables on previously published research by looking at the sources provided to reporters through the subsidy of corporate news releases. The researchers chose to investigate how releases from the top 25 companies on the Fortune 500 list compared to those from the highest-ranked 25 corporations headed by women to determine if releases from women-headed companies would be more likely to quote women as sources." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-19046